Evaluation of the Dutch neonatal screening for congenital adrenal hyperplasia. Issue 7 (2nd February 2019) - van der Linde, Annelieke A A; Schönbeck, Yvonne; van der Kamp, Hetty J; van den Akker, Erica L T; van Albada, Mirjam E; Boelen, Anita; Finken, Martijn J J; Hannema, Sabine E; Hoorweg-Nijman, Gera; Odink, Roelof J; Schielen, Peter C J I; Straetemans, Saartje; et al.
Abstract : Background: In 2002, a nationwide screening for congenital adrenal hyperplasia (CAH) was introduced in the Netherlands. The aim of our study is to evaluate the validity of the neonatal screening for CAH and to assess how many newborns with salt-wasting (SW) CAH have already been clinically diagnosed before the screening result was known. Methods: Retrospective, descriptive study. The following data of patients with positive screening results since implementation of the screening programme were collected (1 January 2002 up until 31 December 2013): gestational age, sex, diagnosis, clinical presentation and contribution of screening to the diagnosis. Results: In the evaluated period, 2 235 931 newborns were screened. 479 children had an abnormal screening result, 133 children were diagnosed with CAH (114 SW, 14 simple virilizing (SV)), five non-classic CAH. During this period, no patients with SW CAH were missed by neonatal screening (sensitivity was 100%). After exclusion of 17 cases with missing information on diagnosis, specificity was 99.98% and positive predictive value was 24.7%. Most false positives (30%) were attributable to prematurity. Of patients with SW CAH, 68% (71/104) patients were detected by neonatal screening and 33 (33/104) were clinically diagnosed. Of girls with SW CAH, 38% (14/37) were detected by neonatal screening and 62% (23/37) were clinically diagnosed. Conclusion: The Dutch neonatal screening has an excellent sensitivity and high specificity. Both boys and girls can benefit from neonatal screening.